IMPLEMENTASI LOGIKA FUZZY MAMDANI UNTUK MENENTUKAN STOK BERAS DI TOKO AGUNG CAHAYA BERBASIS WEB - Yuda; Achmad Lutfi Fuadi (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
How to handle rice stock determination appropriately according to sales To build a system that is able to determine rice stock quickly fuzzy mamdani Make a system design according to ongoing needs through modeling, and make Usecase diagrams, Sequence diagrams, Class diagrams , Design the interface for the user and then proceed with making coding and databases in accordance with the design made. To determine the stock of baras Rice is not only used as rice, but can also be used as raw material for various foods and beverages such as glutinous rice, tapai, and also herbal rice kencur. This fuzzy logic has three methods including the Fuzzy Tsukamoto, Sugeno, and Mamdani methods and from these three fuzzy methods they have different inference and defuzzification engines.